Codonopsis pilosula Polysaccharide Improved Spleen Deficiency in Mice by Modulating Gut Microbiota and Energy Related Metabolisms - Cao, Lingya; Du, Changli; Zhai, Xiaolu; Li, Jiankuan; Meng, Jingyi; Shao, Yunyun; Gao, Jianping (Frontiers in Pharmacology, 2022)
Codonopsis Radix (CR) is an important traditional Chinese medicine used for the treatment of spleen deficiency syndrome (SDS). Codonopsis pilosula polysaccharides (CPP) in CR are considered to be responsible for tonifying the spleen function; however, the mechanisms of the polysaccharides have remained unclear. This study aimed to investigate the treatment mechanisms of CPP in SDS mice using a combinational strategy of 16S rRNA gene sequencing and targeted metabolomics. Here, studies demonstrated that CPP had invigorating effect in vivo in Sennae Folium-induced SDS in mice by organ indexes, D-xylose determination, gastrointestinal hormones levels and goblet cells observation. Antibiotic treatment revealed that the intestinal microbiota was required for the invigorating spleen effect of CPP. Furthermore, gut microbiota analysis found that CPP significantly enriched probiotic Lactobacillus and decreased the abundance of some opportunistic pathogens, such as Enterococcus and Shigella. The metabolic profile analysis of the colonic content revealed that 25 chemicals were altered significantly by CPP, including amino acids, organic acids, fatty acids, carbohydrates and carnitine etc., which are mainly related to “energy conversion” related processes such as amino acids metabolism, tricarboxylic acid cycle, and nitrogen metabolism. Spearman’s correlation assays displayed there were strong correlations among biochemical indicators-gut microbiota-metabolomics. In summary, these results provided a new perspective for CPP improving SDS by regulating energy metabolism related bacteria and pathways.